Class Action Dilemmas Pursuing Public Goals for Private Gain - Hensler, Deborah R. (RAND Corporation, 2000)
Class action lawsuits--allowing one or a few plaintiffs to represent many who seek redress--have long been controversial. The current controversy, centered on lawsuits for money damages, is characterized by sharp disagreement among stakeholders about the kinds of suits being filed, whether plaintiffs' claims are meritorious, and whether resolutions to class actions are fair or socially desirable. Ultimately, these concerns lead many to wonder, Are class actions worth their costs to society and to business? Do they do more harm than good? To describe the landscape of current damage class action litigation, elucidate problems, and identify solutions, the RAND Institute for Civil Justice conducted a study using qualitative and quantitative research methods. The researchers concluded that the controversy over damage class actions has proven intractable because it implicates deeply held but sharply contested ideological views among stakeholders. Nevertheless, many of the political antagonists agree that class action practices merit improvement. The authors argue that both practices and outcomes could be substantially improved if more judges would supervise class action litigation more actively and scrutinize proposed settlements and fee awards more carefully. Educating and empowering judges to take more responsibility for case outcomes--and ensuring that they have the resources to do so--can help the civil justice system achieve a better balance between the public goals of class actions and the private interests that drive them.